Synthetic DNA co-immunization with vaccine-aligned common consensus nucleoprotein and hemagglutinin protects mice against lethal influenza infection with a single immunization - Gary, Ebony N.; Trachtman, Abigail R.; Wang, Dan; Bharti, Suman; Ye, Ying; Tursi, Nicholas J.; Tomirotti, Martina; Eisenhauer, Jillian; Chu, Jacqueline D.; Zegarra, David Custodio; Hojecki, Casey E.; Zheng, Micki; et al. (Frontiers in Immunology, 2025)
IntroductionThere is an urgent need for influenza vaccine strategies that enhance protection against influenza virus drift and across different subtypes. The conserved viral nucleoprotein (NP) is the most abundant viral protein during replication, and a target for broadly protective cellular immune responses.MethodsGuided by annual WHO-recommended seasonal vaccine strains, we engineered synthetic DNA vaccine candidates encoding vaccine-aligned common consensus (VACC) immunogens designed to represent the immune diversity of seasonal H1N1 and H3N2 virus NP proteins (pVACC-NPH1; pVACC-NPH3).ResultsBoth pVACC-NPH1 and pVACC-NPH3 DNA vaccines induced robust cellular immune responses in mice, including the induction of durable responses. Immunization with a single dose of either DNA vaccine 14 days prior to lethal A/California/2009 H1N1 virus challenge provided protection against mortality. Single dose co-administration of pVACC-NPH3 with an HA-expressing DNA vaccine (pHAH1) and plasmid-encoded adjuvant pIL-12 afforded improved protection against morbidity and mortality in a high-dose challenge model.DiscussionThese data highlight the potential of heterologous cellular immunity induced by engineered NP immunogens to complement HA-based approaches to significantly improve challenge outcomes.